2022
DOI: 10.1093/ehjcr/ytac290
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant myocarditis after the first dose of mRNA-1273 vaccination in a patient with previous COVID-19: a case report

Abstract: Background COVID-19 vaccines have shown success in protecting people worldwide, although serious adverse effects have been reported in very rare cases. Case summary A 32-year-old male with a prior medical history of mild COVID-19 infection developed fulminant myocarditis five days after mRNA-1273 vaccination (first dose), which was confirmed using endomyocardial biopsy. He acutely developed respiratory failure and cardiogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…mRNA is one type of novel vaccine and showed great potency. However, it has never been applied for human vaccine production before COVID-19, so its long-term efficiency and safety, especially for myocarditis ( 41 ), need to be further evaluated. Traditional inactivated vaccine can be produced in mature platforms, but the high costs and complicated processes limit its access to vaccination in many middle-income and low-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA is one type of novel vaccine and showed great potency. However, it has never been applied for human vaccine production before COVID-19, so its long-term efficiency and safety, especially for myocarditis ( 41 ), need to be further evaluated. Traditional inactivated vaccine can be produced in mature platforms, but the high costs and complicated processes limit its access to vaccination in many middle-income and low-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Also, according to the US Centers for Disease Control and Prevention, myocarditis/pericarditis rates are described with 13 cases per million doses of second-dose mRNA vaccine [18]. In multiple studies/case reports describing acute myocarditis following COVID-19 mRNA vaccines, however, this adverse event usually occurs shortly after the second dose [8,[19][20][21]. The patients presented with chest pain had elevated cardiac troponin levels, an abnormal ECG with ST elevations in most, and CMR imaging was suggestive of myocarditis in all and none of the patients had evidence of acute COVID-19 [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid onset after vaccination, even after a first dose, would be consistent with such a direct effect. Based on case reports suggesting an increased risk in those vaccinated after infection, together with the increased risk after the second dose, an immune-mediated mechanism involving antibodies to some component of the spike protein has been proposed [23][24][25]. However, our study showed that the vaccine risk was not exacerbated in those who had a prior SARS-CoV-2 infection, nor was the risk increased after a booster dose-scenarios which result in high levels of anti-spike IgG antibodies, particularly in younger adults [26].…”
Section: Plos Medicinementioning
confidence: 99%